2011
DOI: 10.1007/s11095-011-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of IGF-1 and HGF from a Biodegradable Polyurethane Scaffold

Abstract: Purpose Biodegradable elastomers, which can possess favorable mechanical properties and degradation rates for soft tissue engineering applications, are more recently being explored as depots for biomolecule delivery. The objective of this study was to synthesize and process biodegradable, elastomeric poly(ester urethane)urea (PEUU) scaffolds and to characterize their ability to incorporate and release bioactive insulin-like growth factor–1 (IGF-1) and hepatocyte growth factor (HGF). Methods Porous PEUU scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Significant work in this area has been undertaken using the sister compound IGF1 (Jaklenec et al 2008, Chen et al 2009, Sun et al 2011, Kim et al 2012. In one example, Nelson et al (2011) used porous poly(ester urethane)urea scaffolds to demonstrate the long-term delivery of bioactive IGF1 in vitro. Likewise, the Meinel group showed that IGF1 releasing silk fibroin scaffolds initiated chondrogenesis from human mesenchymal stem cells in vitro (Uebersax et al 2008).…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%
“…Significant work in this area has been undertaken using the sister compound IGF1 (Jaklenec et al 2008, Chen et al 2009, Sun et al 2011, Kim et al 2012. In one example, Nelson et al (2011) used porous poly(ester urethane)urea scaffolds to demonstrate the long-term delivery of bioactive IGF1 in vitro. Likewise, the Meinel group showed that IGF1 releasing silk fibroin scaffolds initiated chondrogenesis from human mesenchymal stem cells in vitro (Uebersax et al 2008).…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%
“…hepatocyte growth factor, which may aid in the regenerative process (Nelson et al, 2011), and suggests the next generation of drug delivery in cardiovascular applications beyond drug-eluting stents.…”
Section: Examples Of Biomaterials Applications To Tissue Engineerimentioning
confidence: 99%
“…The simplest version of delivery system is a direct attachment of growth factor to the surface of the scaffold material by soaking the scaffold in growth factor suspension (Kanematsu et al, 2004), or incorporation of the growth factors and cytokines into biodegradable scaffolds, usually hydrogels (Yamamoto et al, 2001;Nelson et al, 2011). The factors are then released passively from the surface of the scaffold or as the scaffold degrades.…”
Section: Direct Attachment or Incorporationmentioning
confidence: 99%